Effect of Occupational Health and Safety on Employee Performance in the Nepalese Construction Industry - Shah, Rekha (Nepalese Journal of Management, 2025)
This study examines the effect of occupational health and safety on employee performance in the Nepalese construction industry. Employee performance is selected as the dependent variable. Similarly, training and development, physical working conditions, safety management, quality of work life and safety culture are selected as the independent variables. This study is based on primary data with 138 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors affecting occupational health and safety on employee performance in the Nepalese construction industry. The study showed that training and development have a positive impact on employee performance. It means that increase in training and development leads to increase in employee performance. Similarly, physical working conditions has a positive impact on employee performance. It indicates that increase in physical working conditions leads to increase in employee performance. Moreover, safety management has a positive impact on employee performance. It means that increase in safety management leads to increase in employee performance. Likewise, quality of work life has a positive impact on employee performance. It shows that increase in quality of work life leads to increase in employee performance. Further, safety culture has a positive impact on employee performance. It shows that higher the safety culture, higher would be the employee performance.